2013
DOI: 10.1136/bjsports-2013-092459.56
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Acute Inflammatory Response and Proliferation of Dry Needling and Electrolysis Percutaneous Intratissue (Epi) in Healthy Rat Achilles Tendons

Abstract: IntroductionElectrolysis Percutaneous Intratissue (EPI) is a new technique that involves the application of a galvanic current with an acupuncture needle that causes a theoretical local inflammatory process and subsequent tissue repair in the soft tissue. Electrolysis Percutaneous Intratissue (EPI) could promote wound healing. The purpose of this study was to examine the cellular response to Dry Needling versus Electrolysis Percutaneous Intratissue (EPI) after intratendinous treatment in an animal model.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Each session will consist of three needle insertions lasting 3 seconds each. In percutaneous needle electrolysis group (PNE-G) applications, an intensity of 3 mA galvanic current will be used during the 3 seconds that the procedure lasts 19. The dose of 3 mA has demonstrated to be as effective as 6 mA in the treatment of tendinopathy injuries in animal models 18 19.…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Each session will consist of three needle insertions lasting 3 seconds each. In percutaneous needle electrolysis group (PNE-G) applications, an intensity of 3 mA galvanic current will be used during the 3 seconds that the procedure lasts 19. The dose of 3 mA has demonstrated to be as effective as 6 mA in the treatment of tendinopathy injuries in animal models 18 19.…”
Section: Methods and Analysismentioning
confidence: 99%
“…In percutaneous needle electrolysis group (PNE-G) applications, an intensity of 3 mA galvanic current will be used during the 3 seconds that the procedure lasts 19. The dose of 3 mA has demonstrated to be as effective as 6 mA in the treatment of tendinopathy injuries in animal models 18 19. In humans, a study conducted in 2016 showed that a dose of 3 mA in PT generated structural changes compatible with tendon regeneration, together with improvement of functionality and pain 22.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Its mechanism of action is electrolysis, or the separation of ions whose charge is opposite to that of the tissue under treatment. This produces a “controlled” injury and an acute inflammatory response leading to the formation of new, healthy tissue [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 This treatment stimulates a local inflammatory response leading to increased cellular activity and repair of the affected area. 9 The needle is directed at the soft tissue injuries of the musculoskeletal system under direct ultrasound visualization. PNE has proven to be effective in tendinosis, 10 plantar fasciitis, 11 whiplash syndrome, 12 and myofascial pain syndrome 13 however, its effectiveness in acute muscle injury is little known.…”
Section: Introductionmentioning
confidence: 99%